Human Factor Position in Rise and Demonstration of Accidents - Holla, Katarina Zanicka; Moricova, Valeria (Communications - Scientific letters of the University of Zilina, 2011)
This article deals with the human being – the human factor and its participation in the rise of industrial disasters (hazard – human error), in preventing their rise (hero – intrepid recoveries) and the way how the accidents affect the people in the form of impacts (victim – accident impact). It is necessary to emphasize also another role of the human factor in the rise of accidents – the solver who takes a share in coping with and managing the disaster, the so called crisis manager who will not be the object of this article. A common feature of all three groups is the psyche of the human factor (personality) and the specific is represented by the different going through and behaving of people during the rise and the course of the accident.